2000
DOI: 10.1111/j.1349-7006.2000.tb00960.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Significance of Expression of CD44 Variants in Head and Neck Squamous Cell Carcinoma

Abstract: Splice variants of the cell surface glycoprotein CD44 have been reported to be associated with the progression of various human tumors. The aim of this study is to determine the correlation between the expression of CD44 isoforms, especially CD44 variant 2 (CD44v2), and the clinicopathological features of head and neck squamous cell carcinomas (HNSCCs). The expression of CD44 isoforms was evaluated immunohistochemically in paraffin-embedded tissues from 89 primary lesions, using monoclonal antibodies against C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(45 reference statements)
1
6
0
1
Order By: Relevance
“…In previous studies, high expression frequencies exceeding 90% have been found in squamous cell carcinomas (SCCs) derived from head and neck, esophagus, skin and lung (10,(17)(18)(19)(20). Our studies are in agreement with those results.…”
Section: Discussionsupporting
confidence: 83%
“…In previous studies, high expression frequencies exceeding 90% have been found in squamous cell carcinomas (SCCs) derived from head and neck, esophagus, skin and lung (10,(17)(18)(19)(20). Our studies are in agreement with those results.…”
Section: Discussionsupporting
confidence: 83%
“…(1998).,[ 12 ] Stoll et al .,[ 13 ] (1999), Kanke et al . (2000).,[ 14 ] Fonseca et al . (2001),[ 15 ] and Ue et al ., (2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, others have reported that down‐regulation of various CD44 variant isoforms correlated with a worse prognosis. Kanke et al reported that down‐regulation of CD44 v2 correlated with poorer differentiation and shorter overall survival, while down‐regulation of CD44 v6 correlated with a higher rate of cervical metastasis 40, 41. Fonseca et al found down‐regulation of CD44 v3 and v6 correlated with tumor grade and pattern of invasion 7.…”
Section: Discussionmentioning
confidence: 99%